Data Security Transmission via a Noisy Channel - K. Mitsophonsiri; S. Punthawanunt; S. Mitatha; P.P. Yupapin (My University, 2011)
We propose a novel method that can be used to perform the data verification and encryption by using the microring resonators incorporating an add/drop filter, where the confidentiality and integrity of information in optical communication can be formed. In this paper, the encryption is formed by the chaotic noise sophisticates irreversible and unpredictable in the nonlinear microring resonator. The proposed system is used to generate the message authentication code for maintaining data integrity, where the noisy signals are created by the microring resonator and combined with the encoded information to protect the man-in-the-middle attacks (decipher). By using the extremely small processing device, the proposed design can be easily applied to secure any form of communication in wireless network, mobile communication network and military applications with low power consumption and very high-speed procedures.
Keywords: DECIPHER; Neural Networks and Reservoir Computing